Fates of potassium during co-pyrolysis of corn stalk and plastic film components - Chao Fan; Jing Liu; Junxia Wang; Jian Li; Zixi Han; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Biomass and Bioenergy, 2027)

Parent material modulates land use effects on soil organic carbon fractions but not inorganic carbon in subtropical red soils - Rui Jiang; Shuai Liu; Yu Zhang; Enze Xie; Beibei Fan; Fahui Jiang; Samuel Adingo; Lei Gao; Xinhua Peng (Soil and Tillage Research, 2026)

An ER-targeted electronic-switched cascade probe for synchronous dual-channel imaging of H2S and HClO during liver fibrosis - Jiaxue Yang; Yi Le; Na Wang; Beibei Wu; Yuyang Song; Ting Wang; Birong Yang; Fan Zhou; Li Liu (Analytica Chimica Acta, 2026)

Lactiplantibacillus plantarum LP15-1 alleviates deoxynivalenol-induced intestinal injury in mice by inhibiting ferroptosis and modulating the gut microbiota - Kunru Teng; Jiefeng Li; Beibei He; Dan Song; Tao Duan; Kuanbo Liu; Lin Qiao; Aike Li; Weiwei Wang; Shijie Fan (Toxicon, 2026)

Biochar-based microbial fertilizer enhances cucumber growth and yield by improving soil quality in protected agriculture - Dongliang Fan; Beibei Zhou; Xiaopeng Chen; Shaoxiong Yao; Manli Duan; Xijun Sun; Wei Hu; Chamindu Deepagoda (Soil and Tillage Research, 2026)

New insights into the temporal speciation of phosphorus during anaerobic digestion of wetland biomass wastes - Fan Yu; Junxia Wang; Zhi Wang; Lan Mu; Xutong Wang; Qianqian Guo; Xiaoqiang Cui; Yanjun Hu; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Stage-dependent roles of Trichoderma longibrachiatum and manganese sulfate in humification and nitrogen conservation during chicken manure composting - Yuchen Yang; Shuzhen Fan; Dan Zhang; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Soil microbial biogeography: from maps to blueprints - Gui-Feng Gao; Shuo Jiao; Ke Dong; Xu Liu; Xin Xin; Beibei Chen; Kunkun Fan; Yu Shi; Congcong Shen; Teng Yang; Minyu Jing; Siyu Chen; et al. (Soil Ecology Letters, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Comparative analysis of wave characteristics between open waters and island-reef waters in China’s near seas - Dongdong Mu; Beibei Zhang; Dajiang Wu; Xiao Liang; Yunsheng Fan (Ocean Engineering, 2026)

Morphology regulation of SBA-15 confined Co-Mo oxides catalyst via a synergetic etching strategy for enhanced oxidative desulfurization - Beibei Zhang; Pengpeng Fan; Lingchao Xu; Xiongyi Yao; Dongao Zhu; Jing He; Chunyan Dai; Wenshuai Zhu; Huaming Li; Wei Jiang (Fuel, 2026)

Detriment of mycotoxin contamination in feed and nutrition-based prevention and control strategies: A review - Shijie Fan; Kunru Teng; Jiefeng Li; Beibei He; Aike Li; Weiwei Wang; Jing Zhang (Toxicon, 2026)

Interface engineering of Si/graphene composites via compression-assisted fast joule heating for enhanced Lithium-ion battery anodes - Pengcheng Deng; Hang He; Tingting Yi; Junfeng Pan; Wenjie Liang; Beibei Yu; Zeman Xie; Zhijun Li; Danish Khan; Zeguo Tang; Xiao Yu; Dongjv Fu; et al. (Chemical Engineering Journal, 2026)

Synergistic defense in cotton: Lignin-mediated barriers and JA/ET signaling pathways against Verticillium wilt - Zhixin Liu; Yinpeng Zhang; Yaping Zhou; Baozhen Wang; Jiani Long; Mengyu Liao; Xiaoli Fan; Wenxuan Kang; Beibei Liu; Xuwu Sun (Plant Science, 2026)

Experimental study on punching shear performance of embedded special-shaped CFST column base - Yong Liu; Zhuofei Li; Jingfeng Wang; Lanhui Guo; Fan Ye; Shasha Tan; Beibei Li (Engineering Structures, 2026)

Fumaric acid restores neomycin efficacy against carbapenem-resistant Vibrio parahaemolyticus through metabolic reprogramming - Ziyi Zhang; Zhuoying Cao; Jiao Fei; Beibei Yan; Ting Zhang; Lvyuan Fan; Wenting Zhang; Chao Wang; Hao Wang; Yubin Su (Journal of Hazardous Materials, 2026)

Multi-omics reveals taxonomic and functional adaptations of soil microbiota to Bt toxin exposure - Luyao Wang; Ziteng Liang; Jingang Liang; Lei Ge; Lingli Zou; Yixuan Fan; Qinqing Xu; Yin Zhang; Beibei Lv; Kai Zhao; Yunfei Wu; Peng Li (Journal of Hazardous Materials, 2026)

Propofol attenuates angiogenesis by activating endoplasmic reticulum stress to suppress TFAP2C-driven VEGFA transcription - Fan Yang; Yi Liu; Hui Li; Xue Shang; Qing Hua; Yun Zhu; Beibei Tao; Zhirong Sun (Apoptosis, 2026)
During anesthesia, significant hemodynamic changes often alter the vascular microenvironment and affecting endothelial cell behavior. Propofol, a commonly used intravenous anesthetic, has been widely studied for its role in tumor angiogenesis through tumor cell–derived VEGF–mediated endothelial interactions. However, its direct effects on endothelial cell–mediated angiogenesis in non-malignant diseases such as diabetic retinopathy, diabetic nephropathy, and coronary heart disease remain unclear. To address this gap, we examined the effects of propofol on VEGFA-mediated angiogenesis in vitro and in vivo. Mechanistically, propofol triggers endoplasmic reticulum stress by promoting phosphorylation of PERK and its downstream effector eIF2α, leading to suppressed translation of TFAP2C—a transcription factor critical for endothelial function. Further analysis revealed that TFAP2C directly binds to the VEGFA promoter to activate its transcription, thereby facilitating VEGFA/VEGFR2-dependent angiogenesis. Together, these findings not only broaden the understanding of propofol’s pharmacological profile, but also identify TFAP2C as a novel transcriptional regulator of VEGFA, offering new perspectives for therapeutic targeting of VEGFA-mediated angiogenesis. Graphical abstract Schematic representation of the mechanism of propofol inhibition of VEGFA/VEGFR2-associated angiogenesis via the PERK/eIF2α/TFAP2C axis.

Synergistic Enhancement of Cobalt Adsorption by Graphitization and Magnetic Modification of Biochar: Synthesis, Characterization, Performance and Mechanism - Hui Liu; Chen Li; Zhichao Fan; Zhirui Dou; Beibei Lu; Xiao Fan; Xiaohui Ji; Jinlong Lai; Qian Fu; Songlin Gong; Xinna Wang; Jie Liu (Water, Air, & Soil Pollution, 2025)

Evolution of phosphorus during co-pyrolysis of wheat straw and mulch film components - Chao Fan; Junxia Wang; Yuxin Yang; Jian Li; Xiaoqiang Cui; Zhanjun Cheng; Beibei Yan; Guanyi Chen; Jingang Yao (Chemical Engineering Journal, 2025)

Carbon dots as an emerging antibacterial agent: Antibacterial mechanism and synthetic optimization - Beibei Wang; Gang Zhou; Qingshan Shi; Weihua Fan; Xiaobao Xie (Journal of Environmental Chemical Engineering, 2025)

Solar-driven bipolar hydrogen production using a large-grain Sb2S3 photocathode coupled with a Cu2O anode - Kuang Feng; Bin Zhao; Zeyu Fan; Ronghua Li; Beibei Zhang; Yanbo Li (Chemical Engineering Journal, 2025)

Pretreatment approaches for mitigating drought stress in plants - Zhenqi Liao; Hatem Boubakri; Beibei Chen; Muhammad Farooq; Tianyi Yang; Qiao Liu; Junliang Fan (South African Journal of Botany, 2025)

From biodegradation to biohazard: Polylactic acid microplastics induced rice growth inhibition in agroecosystems - Bigui Lin; Qingfang Fan; Fang Liu; Luya Wang; Chaoxian Wei; Beibei Liu; Juan Zhao; Linzi Zuo; Yi Xie (Journal of Hazardous Materials, 2025)

The overexpression of DgPR1 enhances chrysanthemum cold tolerance through the ROS-mediated pathway - Yuchen Tian; Yan Feng; Yongyan Wang; Qingwu Deng; Xuanling Luo; Fan Zhang; Lei Zhang; Beibei Jiang; Qinglin Liu (Plant Science, 2025)

Reclamation of available phosphorus and separation of heavy metals from sewage sludge via FeCl3-assisted electrokinetic treatment and pyrolysis - Xutong Wang; Huwei Li; Junxia Wang; Wolfram Buss; Anna Bogush; Ondřej Mašek; Youjun Zhang; Fan Yu; Beibei Yan; Zhanjun Cheng; Xiaoqiang Cui; Guanyi Chen; et al. (Journal of Environmental Management, 2025)

A review on the production of nutrient-enriched biochar: Insights from the evolution of nitrogen, phosphorus, and potassium - Xiaoqiang Cui; Xufeng Li; Junxia Wang; Xutong Wang; Fan Yu; Gaixiu Yang; Shiwei Xu; Zhanjun Cheng; Qianying Yang; Beibei Yan; Guanyi Chen (Critical Reviews in Environmental Science and Technology, 2025)

Flexible gustatory artificial synapses based on tribotronic organic electrochemical transistor - Yongbo Li; Junqing Zhao; Feiling Luo; Jianhua Zeng; Beibei Fan; Tianrui Dang; Weilin Zhou; Yiming Dai; Jie Cao; Chi Zhang (Chemical Engineering Journal, 2025)

The regulatory role of phytohormones in plant drought tolerance - Zhenqi Liao; Beibei Chen; Hatem Boubakri; Muhammad Farooq; Luis Alejandro Jose Mur; Daisuke Urano; Chee How Teo; Boon Chin Tan; MD Mahadi Hasan; Mehtab Muhammad Aslam; Muhammad Yahya Tahir; Junliang Fan (Planta, 2025)

NDO-enhanced adaptive fixed-time prescribed performance sliding mode tracking control for coaxial cross-domain flying buoys under unknown ocean disturbances - Mingqing Lu; Menglei Tu; Fei Liao; Shichong Wu; Beibei Xing; Zhaolin Fan; Yumin Su; Wenhua Wu (Ocean Engineering, 2025)

The association between outdoor artificial light at night exposure and antenatal depression and anxiety symptoms: A retrospective cohort study in China - Jingjing Liu; Yidan Cao; Tuyan Fan; Jiawen Zhao; Tianli Zhu; Hui Gao; Fangbiao Tao; Beibei Zhu (Environmental Research, 2025)

Bt toxins alter bacterial communities and their potential functions in earthworm intestines - Luyao Wang; Yixuan Fan; Lingli Zou; Lei Ge; Wei Jiang; Shengqian Chao; Beibei Lv; Kai Zhao; Jun Chen; Peng Li (Environmental Pollution, 2025)

Biofertilizers as an eco-friendly approach to combat drought stress in plants - Zhenqi Liao; Hatem Boubakri; Beibei Chen; Muhammad Farooq; Zhenlin Lai; Hongtai Kou; Junliang Fan (Biocatalysis and Agricultural Biotechnology, 2025)

The effects of small plastic particles on antibiotic resistance gene transfer revealed by single cell and community level analysis - Yuqiu Luo; Tiansi Xu; Bing Li; Fan Liu; Beibei Wu; Phil S. Dobson; Huabing Yin; Zheng Chen; Yong Qiu; Xia Huang (Journal of Hazardous Materials, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Additive patterns in near-infrared diffuse reflectance spectra: Implications for product formulation and analysis - Le Zhao; Youyan Liang; Nuohan Zhang; Yanbin Chang; Meijuan Fan; Cong Wang; Beibei Li; Hongbo Wang; Yu Liu; Hongxiao Yu; Song Yang; Fuwei Xie; et al. (Food Control, 2024)

Rapid Joule heating-induced welding of silicon and graphene for enhanced lithium-ion battery anodes - Fan Yang; Pengcheng Deng; Hang He; Ruolan Hong; Kun Xiang; Yuan Cao; Beibei Yu; Zeman Xie; Jiming Lu; Zikang Liu; Danish Khan; David Harbottle; et al. (Chemical Engineering Journal, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Characterizing superlubricity by tribovoltaic effect - Zhaozheng Wang; Kai Gao; Yuan Feng; Jie Cao; Likun Gong; Beibei Fan; Yi Zhang; Guoxin Xie; Chi Zhang (Science Bulletin, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Pyrolysis characteristics and kinetics of waste photovoltaic module: A TG-MS-FTIR study - Fan Li; Junyu Tao; Akash Kumar; Jia Zhang; Yunan Sun; Wei Guo; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Journal of Cleaner Production, 2024)

Coupling electrokinetic technique with hydrothermal carbonization for phosphorus-enriched hydrochar production and heavy metal separation from sewage sludge - Xutong Wang; Ondřej Mašek; Huwei Li; Fan Yu; Christian Wurzer; Junxia Wang; Beibei Yan; Xiaoqiang Cui; Guanyi Chen; Li'an Hou (Chemical Engineering Journal, 2024)

On-site detection of Sporothrix globosa using immunoglobulin Y, magnetic separation and loop-mediated isothermal amplification - Beibei Fan; Xiangyang Zhuang; Jia Wei; Liangyun Bu; Yanwen Liu; Liang Zhang; Mingrui Zhang; Juan Li; Bo Pang (Analytica Chimica Acta, 2024)

Higher mechanical stability and mutual-stabilizing/confining effect enables anti-pulverization SbSn alloy/N-doped porous carbon with high-performance in sodium-based dual-ion batteries - Fan Zhang; Hui Wang; Xiaojie Liu; Gang Wang; Beibei Wang (Chemical Engineering Journal, 2023)

Coastal sediment heavy metal(loid) pollution under multifaceted anthropogenic stress: Insights based on geochemical baselines and source-related risks - Zexing Kuang; Huijuan Wang; Beibei Han; Yiyong Rao; Haixing Gong; Wanru Zhang; Yangguang Gu; Zhengqiu Fan; Shoubing Wang; Honghui Huang (Chemosphere, 2023)

Porphyrin-based metal-organic frameworks enhanced electrochemiluminescence (ECL) by overcoming aggregation-caused quenching: A new ECL emitter for the detection of trenbolone - Beibei Wang; Lu Zhao; Yuyang Li; Xuejing Liu; Dawei Fan; Dan Wu; Qin Wei (Analytica Chimica Acta, 2023)

Instance segmentation method for weed detection using UAV imagery in soybean fields - Beibei Xu; Jiahao Fan; Jun Chao; Nikola Arsenijevic; Rodrigo Werle; Zhou Zhang (Computers and Electronics in Agriculture, 2023)

Enhanced phosphorus fixation in red mud-amended acidic soil subjected to periodic flooding-drying and straw incorporation - Shuai Ding; Tiantian Zhang; Beibei Fan; Bingqian Fan; Junhui Yin; Shuo Chen; Shuai Zhang; Qing Chen (Environmental Research, 2023)

Unveiling “Sabatier principle” for electrocatalytic nitric oxide reduction on single cluster catalysts: A DFT and machine learning guideline - Lei Yang; Jiake Fan; Beibei Xiao; Weihua Zhu (Chemical Engineering Journal, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Phosphorus transformation behavior and phosphorus cycling genes expression in food waste composting with hydroxyapatite enhanced by phosphate-solubilizing bacteria - Shaoqi Xu; Kaixue Jia; Yi Zheng; Wenjie Chen; Zhigang Wang; Dan Wei; Baoru Sun; Meidi Cheng; Beibei Fan; Ji Li; Yuquan Wei (Bioresource Technology, 2023)

Comprehensive understanding of guest compound intercalated layered double hydroxides: Design and applications in removal of potentially toxic elements - Shihao Cui; Yutao Peng; Xiao Yang; Xing Gao; Chung-Yu Guan; Beibei Fan; Xue Zhou; Qing Chen (Critical Reviews in Environmental Science and Technology, 2023)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Effects of phosphorus-containing material application on soil cadmium bioavailability: a meta-analysis - Yi Tan; Xue Zhou; Yutao Peng; Zijing Zheng; Xing Gao; Yan Ma; Shuo Chen; Shihao Cui; Beibei Fan; Qing Chen (Environmental Science and Pollution Research, 2022)

Effect of organic acid amendment on secondary saline soil amelioration in gully land consolidation area in northern Shaanxi, China - Yang Yang; Manli Duan; Beibei Zhou; Xiaoqing Li; Lu Yang; Chaofan Liang; Fan Xiao (Arabian Journal of Geosciences, 2020)

Nuclear miR-665 aggravates heart failure via suppressing phosphatase and tensin homolog transcription - Jiahui Fan; Xudong Zhang; Xiang Nie; Huaping Li; Shuai Yuan; Beibei Dai; Jiabing Zhan; Zheng Wen; Jiangang Jiang; Chen Chen; Daowen Wang (Science China Life Sciences, 2020)